2017
DOI: 10.1016/j.psep.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel acoustic emission detection module for leakage recognition in a gas pipeline valve

Abstract: Internal valve leakage in a natural gas pipeline seriously impairs the safe operation on pipelines, and the recognition of leakages has therefore been a major concern of the industry. In this study, a novel leakage detection scheme based on kernel principal component analysis (kernel PCA) and the support vector machine (SVM) classifier for the recognition of the leakage level is constructed. Using this approach, the acoustic signal of the leakage is obtained as the feature source using an acoustic emission (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In general, features regarding the AE signals include two main categories in the time domain and the frequency domain. The most commonly used features (Li et al., 2016) are listed in Table 1, where X=[x1,x2,,xm] denotes an AE signal in the time domain and F=[f1,f2,,fn] denotes amplitude in the frequency domain with Xf=[xf1,xf2,,xfn].…”
Section: Methodsmentioning
confidence: 99%
“…In general, features regarding the AE signals include two main categories in the time domain and the frequency domain. The most commonly used features (Li et al., 2016) are listed in Table 1, where X=[x1,x2,,xm] denotes an AE signal in the time domain and F=[f1,f2,,fn] denotes amplitude in the frequency domain with Xf=[xf1,xf2,,xfn].…”
Section: Methodsmentioning
confidence: 99%
“…The AE-based leak detection is therefore feasible. Consequently, many researchers have applied this mechanism to detect a leak in a gas pipeline [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The leak detection using AE signals is extremely beneficial because it is a non-destructive technique, thus it does not affect the working system [ 5 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results demonstrated that the discretization approach significantly reduced the calculated amount. 5 Li et al 6 presented the acoustic emission sensor for leakage detection based on kernel principal component analysis and support vector machine classifier, which were used for the optimal feature extraction and the recognition of the leakage level, respectively. However, the methods mentioned above could not detect hydrate plugging and pipeline leak simultaneously.…”
Section: Introductionmentioning
confidence: 99%